Comparison of slow and forced vital capacities on ability to predict survival in ALS. Issue 7 (2nd October 2017) - Pinto, Susana; de Carvalho, Mamede
Abstract: Introduction : Slow (SVC) and forced (FVC) vital capacities are the most used pulmonary function tests in amyotrophic lateral sclerosis (ALS). It is unknown if they equally predict survival in ALS. The aim of the present study was to compare both measures in predicting survival in this disease. Methods : Consecutive definite/probable ALS patients (2000–2014) in whom respiratory tests were performed at baseline and four months later were included. All patients were evaluated with the revised ALS functional rating scale (ALSFRS-R), respiratory (RofALSFRS-R), bulbar (ALSFRSb), upper and lower limb subscores, SVC, FVC, maximal inspiratory (MIP) and expiratory (MEP) pressures. King's functional staging system was applied retrospectively. Survival analysis was carried out by univariate Kaplan-Meier log-rank test. Multivariate Cox proportional hazards model determined significant independent variables. Results : We included 469 patients (270 males; mean onset age 61.0 ± 11.5 years; mean disease duration from first symptoms to first visit: 15.8 ± 16.1months; 329 spinal and 140 bulbar onset). FVC and SVC were strongly correlated ( r 2  = 0.981, p  < 0.001). Significant survival prognostic variables (Kaplan-Meier analyses) were onset region, age, disease duration, ALSFRS-R, ALSFRSb, RofALSFRS-R, ALSFRS-R decay, SVC, FVC, MIP, MEP and King's staging ( p  ≤ 0.01). Final Cox model including the significant variables showed similar results for FVC and SVC ( p  < 0.001). Moreover, 1% decrease in either predicted values increased death probability by 1.02. Conclusion : FVC and SVC are inter-changeable in predicting survival in ALS.